Haemophilus influenzae e Haemophilus haemolyticus isolados de crianças que frequentam creches no município de Goiânia-GO: prevalência, fatores de risco e caracterização molecular da resistência antimicrobiana - Almeida, Robmary Matias de (2017)
Haemophilus influenzae (Hi) and Haemophilus haemolyticus (Hhae) are important microorganisms present in human nasopharyngeal colonization, with rates varying according to locality, sampling frequency, individual and social factors. Hi is a pathological agent that causes diseases such as meningitis, pneumonia, sepsis and otitis media, which presents in encapsulated forms with six serotypes a, b, c, d, e, f, and uncapsulated or non-typeable (HiNT). Hhae is a nasopharyngeal comensal and rarely causes invasive diseases. The objective of this study was to estimate the prevalence of Hi and Hhae in children under five years of age attending public day care centers in the city of Goiânia-GO, to determine the circulating serotypes, to analyze the risk factors associated with the nasopharyngeal carrige, as well as to characterize the antimicrobial resistance of Hi. Were analyzed 1.188 nasopharynx swabs from healthy children between 36 and 59 months of age from October to December 2010. The samples were submitted to bacterial culture for the isolation of Haemophilus spp. For the identification of the species, the Real-Time Polymerase Chain Reaction (TR-PCR) was used. Serotyping, as well as detection of the bla TEM-1 and bla ROB-1 resistance genes, was performed through the conventional Polymerase Chain Reaction. Phenotypic detection for β-lactamase production was performed by the chromogenic cephalosporin test. The database was constructed with the statistical software SPSS (Chicago, IL, USA) version 18.0. Risk factors, children aged 3 years, low maternal schooling and three or more children under 10 years of age living in the same household of the child recruited in the study were evaluated by multivariate Poisson regression. The prevalence of Hi carriers was 54.4% (646 / 1.188), 0.9% (n = 11) of the serotype e, 0.9% (n = 11) of serotype f, 0.2% (n = 2) serotype a, 0.08% (n = 1) serotype d, 0.0% (n = 0) serotype b and c and 52.3% (621 / 1.188) of HiNT. The prevalence of Hhae was 1.2% (14 / 1.188). Among the encapsulated Hi, the prevalence of the bla TEM-1 gene was 4.0% (1/25) and the bla ROB-1 gene was 4.0% (1/25). Among the 20% (124/621) of HiNT analysed, the prevalence of the bla TEM-1 gene was 13,7% (17/124) and the prevalence of the bla TEM-1 gene was 1,6% (2/124). Continuous surveillance of Haemophilus spp. as a colonizer, is necessary to evaluate its transmission and dissemination in the population where there is a higher risk of invasive disease, to control Hib re-emergence after the vaccinacion and to continue to monitor antimicrobial resistance.